2023
DOI: 10.1134/s0006297923050012
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Orchestrate Adult Hippocampal Plasticity: Growth Points and Translational Aspects

Abstract: The review analyzes modern concepts about the control of various mechanisms of the hippocampal neuroplasticity in adult mammals and humans by glucocorticoids. Glucocorticoid hormones ensure the coordinated functioning of key components and mechanisms of hippocampal plasticity: neurogenesis, glutamatergic neurotransmission, microglia and astrocytes, systems of neurotrophic factors, neuroinflammation, proteases, metabolic hormones, neurosteroids. Regulatory mechanisms are diverse; along with the direct action of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 156 publications
0
3
0
Order By: Relevance
“…In addition, in adult mammals and humans, it has been demonstrated that neuroplasticity, which is controlled through various mechanisms, is influenced by GC stress. As expected, regulated levels of blood GCs are closely associated with brain function by affecting hippocampal plasticity, including glutamatergic neurotransmission, neurogenesis, systems of neurotrophic factors, microglia, astrocytes, neuroinflammation, and so on [35]. In addition to the amygdala and hippocampus, the prefrontal cortices are involved in the corticolimbic system and are perturbed by the abnormal function of BDNF/TrkB-related signaling and activity of GR [36].…”
Section: Glucocorticoid Stress Bdnf and Neuronal Functionsmentioning
confidence: 60%
“…In addition, in adult mammals and humans, it has been demonstrated that neuroplasticity, which is controlled through various mechanisms, is influenced by GC stress. As expected, regulated levels of blood GCs are closely associated with brain function by affecting hippocampal plasticity, including glutamatergic neurotransmission, neurogenesis, systems of neurotrophic factors, microglia, astrocytes, neuroinflammation, and so on [35]. In addition to the amygdala and hippocampus, the prefrontal cortices are involved in the corticolimbic system and are perturbed by the abnormal function of BDNF/TrkB-related signaling and activity of GR [36].…”
Section: Glucocorticoid Stress Bdnf and Neuronal Functionsmentioning
confidence: 60%
“…Our results suggest that the GCS ambiguously modulate specific aspects of neuroinflammatory response in the hippocampus on both molecular and cellular levels. Directly or indirectly, both GCS and neuroinflammatory processes are involved in virtually all mechanisms of hippocampal neuroplasticity [ 30 ], and the routes of this control by GCS are obviously much more intricate than what we can hypothesize based on available but yet obviously incomplete experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids, executive hormones of HPA axis ensure the coordinated functioning of key components and mechanisms of brain plasticity at different levels, including neurogenesis, glutamatergic neurotransmission, microglia and astrocytes, systems of neurotrophic factors, neuroinflammation, etc. [69]. Adaptation to chronic hyperactivation of the HPA axis may lead to loss of the system sensitivity through chronic activation of negative feedback and feed-forward regulators.…”
Section: Discussionmentioning
confidence: 99%